Microsecond pulsed yellow emission by intracavity doubled optically pumped two-chip VECSEL. (9th March 2023) - Liu, Hua-Yu; Ma, Hao-Da; Bian, Qi; Bo, Yong; Cui, Da-Fu; Peng, Qin-Jun
Abstract: A quasi-continues-wave (QCW) 100 μ s pulsed yellow laser at 589 nm, based on intracavity frequency doubling (ICFD) of identical two-chip vertical-external-cavity surface-emitting laser (VECSEL) with bow-tie configuration, is demonstrated. Each VECSEL chip is optically QCW-pumped by an 808 nm laser diode, emitting a fundamental wavelength around 1178 nm. A birefringence filter is inserted in the laser cavity to select the linear p-polarized oscillation and tune the operation wavelength. Using a lithium-triborate (LiB3 O5 ) as the frequency doubled crystal, a total frequency doubled output power of 264 mW at 589 nm is achieved, operating at a pulse duration of 194 μ s and a pulse repetition rate of 1 kHz. A good beam quality factor is measured to be M 2 = 2.15. These results represent a novel scheme for the QCW multiple gain chips VECSEL ICFD system, opening up a new perspective for the realization of impact long pulse 589 nm laser for sodium guide-star.